Job Stress and Employees' Satisfaction in the Hospitality and Tourism Sector of North East India - Nirmal Chandra Roy (Centre For Tourism Planning and Development, 2023)
In the modern times, the demand for hotel and tourism services is increasing rapidly. As a result, hospitality employees face enormous professional pressure at work. This work pressure causes them stress at work. Since job satisfaction is a prerequisite for providing the highest quality services, it largely depends on the level of stress in the workplace. In this study, determinants of job stress have been identified first and then an attempt has been made to study the impact of job stress on employees’ satisfaction. The study has been conducted with the help of primary data collected from the sample respondents from the study region. The study applies factor analysis and multiple regression analysis. The study confirmed that Eustress has direct positive relations with the job satisfaction of employees. Since, the study reveals that Duration of Work (DW), Job Profile (JP), and Expectation of Management (EM) have positively influenced job satisfaction. HR Policy (HRP) and Work Pressure (WP) negatively affected job satisfaction and these aspects should be taken care of by the management.